(untitled) (Eurasian Journal of Religious Studies, 2019)
The article examines the issues of Islamic education in the context of a secular state policy, as well as issues related to religious education and the role of Islamic education in the formation of ideological values. As we have seen from the world practice, many countries have chosen the direction of secular development. But education secularism does not mean that religious education can not be tolerated. On the contrary, within the framework of the secular laws of the country, there is a unique opportunity for religious education. At present, religious education refers to the teaching of religious leaders in religious institutions. The article discusses the history of Islamic education’s birth on the example of Kazakhstan and other countries and notes the role of Islamic education in the territory of Kazakhstan. The policy of the secular state of Kazakhstan does not hinder the functioning of religion, but on the contrary forms the traditional understanding of traditional Islam and gives a national character. In many civilized countries of the world, religious education institutions have long been systematically conducted. In the process of globalization, each state strives to preserve its national values and national identity.